Using RNA-Seq to assemble a rose transcriptome with more than 13,000 full-length expressed genes and to develop the WagRhSNP 68k Axiom SNP array for rose (Rosa L.) - Koning-Boucoiran, Carole F. S.; Esselink, G. Danny; Vukosavljev, Mirjana; van 't Westende, Wendy P. C.; Gitonga, Virginia W.; Krens, Frans A.; Voorrips, Roeland E.; van de Weg, W. Eric; Schulz, Dietmar; Debener, Thomas; Maliepaard, Chris; Arens, Paul; et al. (Frontiers in Plant Science, 2015)
In order to develop a versatile and large SNP array for rose, we set out to mine ESTs from diverse sets of rose germplasm. For this RNA-Seq libraries containing about 700 million reads were generated from tetraploid cut and garden roses using Illumina paired-end sequencing, and from diploid Rosa multiflora using 454 sequencing. Separate de novo assemblies were performed in order to identify single nucleotide polymorphisms (SNPs) within and between rose varieties. SNPs among tetraploid roses were selected for constructing a genotyping array that can be employed for genetic mapping and marker-trait association discovery in breeding programs based on tetraploid germplasm, both from cut roses and from garden roses. In total 68,893 SNPs were included on the WagRhSNP Axiom array. Next, an orthology-guided assembly was performed for the construction of a non-redundant rose transcriptome database. A total of 21,740 transcripts had significant hits with orthologous genes in the strawberry (Fragaria vesca L.) genome. Of these 13,390 appeared to contain the full-length coding regions. This newly established transcriptome resource adds considerably to the currently available sequence resources for the Rosaceae family in general and the genus Rosa in particular.